The impact of maternal working conditions on fetal weight: a risk factor for fetal growth restriction? - Trocado,Vera (2020)
Overview and aims: Several risk factors for fetal growth restriction (FGR) have been described, however the impact of maternal working conditions is still poorly understood. To evaluate the impact of type of transport used, travel time, weekly hours of work, shift work, posture, environmental conditions, physical load and occupational stress on fetal weight. Study design and population: A case-control study was conducted. All professionally active pregnant woman that attended during 3rd trimester a pregnancy surveillance consultation at two Portuguese public hospitals during 4 months were included. The population was divided in two groups: FGR group - fetuses with estimated fetal weight (EFW) below the 10th percentile at 3rd trimester ultrasound; control group - fetuses with EFW equal to or higher than 10th percentile at 3rd trimester ultrasound. Methods: Data about working conditions, anthropometric and sociodemographic characteristics were collected using a questionnaire and the occupational stress questionnaire-general version (QSO-VG). Data on obstetric characteristics was acquired from clinical records. Data analysis was performed using SPSS ®, version 22.0. Results: There were 50 pregnant women in the FGR group and 295 in the control group. A predictive model of FGR was developed including 5 variables - sitting for at least 3 hours, high occupational stress levels, work by shifts, shifts with daytime and night rotation and load or lift weights greater than or equal to 25 Kg - with high specificity (98,5%), a positive predictive value of 85.7% and a negative predictive value of 74.2%, but with a low sensitivity (20.7%). Conclusions: This study showed that maternal working conditions can be important predictors of FGR.